CONCEPTUAL BASIS OF COMMUNICATION MANAGEMENT - V. Pryimak; V. Balan (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper describes conceptual components of communication management, gives several practical recommendations in relation to communication engineering of the main business processes and defines the complex of communicative competence for the specialist in communication management according to the CM-oriented paradigm of community development.